1994
DOI: 10.1523/jneurosci.14-03-01011.1994
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic properties of serotonergic growth cones in developing rat brain

Abstract: In order to gain insight into the events that take place when serotonergic growth cones are remodeled into synapses, we tested the hypothesis that neurotransmitter-related properties of presynaptic terminals are already present in these growth cones before synaptogenesis begins. The ontogeny of markers for the specific reuptake of 5-HT and for 5-HT-storing synaptic vesicles was studied in isolated growth cone (IGC) fractions from developing rat brain. High- affinity 3H-imipramine binding (a marker for the plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 98 publications
(139 reference statements)
6
29
0
Order By: Relevance
“…3D). The ultrastructure of some 5-HTϩ profiles closely resembled that of serotonergic growth cones, as described by Igvy-May et al (1994). They contained small and large densecored vesicles, as well as large vacuoles (Fig.…”
Section: Resultssupporting
confidence: 69%
“…3D). The ultrastructure of some 5-HTϩ profiles closely resembled that of serotonergic growth cones, as described by Igvy-May et al (1994). They contained small and large densecored vesicles, as well as large vacuoles (Fig.…”
Section: Resultssupporting
confidence: 69%
“…Ontogenesis of the rat 5-HT transporter and 5-HT receptors indicates a rapid increase during the perinatal and early postnatal period to reach adult levels by the end of the third postnatal week, with a time course that closely parallels synaptogenesis (Igvy-May et al, 1994). Recently, many investigations have been devoted to the exploration of the neurobehavioral and neurochemical effects of developmental exposure to SSRIs, and most research has focused on fluoxetine because of its high selectivity and negligible affinity for several receptor subtypes.…”
Section: Selective Serotonin Reuptake Inhibitorsmentioning
confidence: 99%
“…Tryptophan hydroxylase (TPH) is the rate-limiting enzyme in the production of serotonin, and during development, brain serotonin levels and TPH mRNA increases 35-fold in DR between embryonic day 18 and PN22 in rat (Rind et al, 2000). Likewise, the level of SERT mRNA, the primary means of removing serotonin from the synapse and Lasting neonatal SSRI effects on 5HT circuits D Maciag et al terminating serotonin signaling, has been found to be related to synaptogenesis (Ivgy-May et al, 1994;Hansson et al, 1998). In human brain, serotonergic neurons have been detected by 5 weeks of gestation and synaptic levels of serotonin increase during the first 2 years after birth and then decrease to adult levels after the age of 5 years (Sodhi and Sanders-Bush, 2004).…”
Section: Introductionmentioning
confidence: 99%